Systematic Literature Review : Penerapan VIKOR Dalam Sistem Pendukung Keputusan - Amanda, Ryan; Leoni, Sonya (Journal of Information System and Education Development, 2025)
This study presents a Systematic Literature Review (SLR) on the application of the VIKOR method in multi-criteria decision-making (MCDM) within the context of Decision Support Systems (DSS). VIKOR is widely acknowledged as a powerful tool for generating compromise solutions when dealing with alternatives that involve conflicting criteria. The primary objectives of this review are to identify the key benefits of applying the VIKOR method, to analyze the common challenges encountered during its implementation in various domains, and to explore how the method has been modified or integrated with other decision-making approaches to improve its effectiveness. The literature was gathered through Google Scholar, applying strict inclusion criteria that focused on peer-reviewed articles published between 2020 and 2024. Out of an initial pool of 50 articles, 10 high-quality and relevant studies were selected for detailed analysis. The results indicate that VIKOR offers substantial advantages in handling complex and non-commensurable criteria, making it well-suited for DSS applications. However, challenges such as dependency on accurate criteria weighting, computational complexity, and difficulty in interpreting compromise conditions persist. Notably, the integration of VIKOR with methods such as AHP, FUCOM, ELECTRE, and ROC has been shown to enhance decision quality and robustness. These findings contribute to the development of more adaptive, transparent, and data-driven DSS models for future implementation..